Jogo de tabuleiro para o ensino de circuitos elétricos - Souza, Paulo José Marques de (2020)
Master's dissertation submitted to the Federal University of Alagoas Graduate Program in the Professional Master's Degree in Physics Education (MNPEF), as part of the necessary requirements to obtain the title of Master in Physics Education. It is recurrent in the literature the fact that many students say they do not like Physics. In addition, many students also say that they can’t understand it, others see it only as other type of mathematics. This kid of things make very difficult the task of making students understand what Physics really is, and not only that, but also getting excited when studying it, what is a great challenge for physics teachers. Because of this, and of the fact that more and more teachers are trying to find more efficient ways of transmitting knowledge to students during classes, many teachers have tried to use several didactic tools in their physics classes. In addition, in general, students find it difficult to learn the name of the basic components of a electric circuit, as well as how to connect the instruments to perform electrical measurements. It was thinking about these issues, that we decided to develop a board game, to be used in classes to teaching about electrical circuits, which was both an interesting didactic tool to be used in the classroom to make the class more dynamic, as well as helping students in learning the contents related to electrical circuits. From the application of the game that we did in three high school classes, at two public schools in Sergipe, we saw that the game had a great acceptance by students. The vast majority of them said that the game helped them to better understand the content about electrical circuits, and helped them to understand when a circuit is in series or in parallel, as well as, to identify the correct position of the instruments measures. The students also said that the rules of the game were easy, and that the game has a good design. Finally, it is worth noting that it is a relatively fast game, which can be played in a 50-minute class, and is inexpensive, since the teacher can print the board, cards and even the dice that are used in the game. Thus, we believe that it will be a very useful teaching tool, both to be applied in private and public schools. We also hope that, in classes where this game will be used, it can increase students' taste for Physics.